(untitled) (UKLO Proceedings, 2026)
Introduction: According to the 2030 Agenda, "To achieve sustainable development, peace and security are necessary; and peace and security will be at risk without sustainable development." The paper will contribute to building Security, peacebuilding and resilience in the context of sustainable development. Methods: When preparing the paper, the author uses general methods, including descriptive, normative, comparative, and content analysis methods. Results: In the final part of the paper, the author concludes that the Global Initiative against Transnational Organized Crime builds a global strategic approach to tackling organized crime by strengthening political commitment to addressing the challenge, building an evidence-based base on organized crime, and developing networks of resilience in affected communities. Discussion: The widening gap between crime authorities and resilience efforts highlights the urgent need to adopt practical strategies to combat organized crime globally. A primary tool for combating organized crime is the ability to develop and manage an effective response strategy.